Growth and development of oil palm seedlings response on water stress at Pertubuhan Peladang Kawasan Kota Tinggi Timur / Muhamad Faiz Muhamad Fadil - Muhamad Fadil, Muhamad Faiz (Faculty of Plantation and Agrotechnology, 2019)
Oil palm or in scientific name is known as Elaeis Guineensis is a major crop that most popular planted in Malaysia. Oil palm also known as very sensitive crop that need good management practices to produce the best quality of the yields. The management started from the nursery stage. At the nursery, water is the essential requirement that needed for plant growth. Oil palm seedlings in the pre nursery need 0.5 L water while in the main nursery the oil palm seedlings should get 2.0 L per day. Besides, water also can lead the oil palm seedlings to stress. There are many factors that can cause the water stress such as drought and raining season and poor irrigation system. This experiment is focused on growth and development of oil palm seedlings in response to water stress conditions. After soil water holding test have been made, the oil palm seedlings is transferred to the sandy loam soil in the polybags. Then, the experiment is carried out by using complete randomize with four water levels that measured as water stress which were control that give enough water for the seedlings, excess water level from control, partially flooding and continuously flooding condition. Then, growth and development of the seedlings based on parameter such as plant height, diameter, number of leaves, roots length and dry weight were measured. From the experiment, significant change is occurred but the best result of seedlings even face the water stress is on control because it has the highest result on the most of measured parameter.